PENGARUH BENZYL AMINO PURIN (BAP) TERHADAP INDUKSI TUNASEKSPLAN TANGKAI DAUN (Petiolus) DAN TULANG DAUN (Penninervis) DUKU (Lansium domesticum Corr) PADA MEDIA MURASHIGE AND SKOOG - ARIF YACHYA; Amin Nurokhman; Linda Novitasari; Ummi Hiras Habisukan (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2023)
Duku (Lansium domesticum. Corr) is one of the fruit plants that grows a lot in Indonesia, especially in South Sumatra. Duku fruit has a fairly high level of consumption but takes a long time to reproduce. Modern duku propagation is an effort that can be used to overcome problems that occur in conventional duku cultivation. One of the efforts to propagate duku in a modern way can be done through tissue culture techniques. Tissue culture techniques can produce plants in large quantities and have the same characteristics and characteristics as the parent. This research was conducted from September 2022 – November 2022, taking place in the tissue culture room, the Integrated Laboratory of Raden Fatah State Islamic University Palembang. This type of research is descriptive quantitative with experimental method using Completely Randomized Design (CRD) with 5 treatments (0.0 ppm, 1.0 ppm, 1.5 ppm, 2.0 ppm and 2.5 ppm) and 5 repetitions. This study was to determine the response of petiole and leaf bone explants to tuna induction by BAP hormone administration. The best research results were given a concentration of 1.0 ppm BAP with growth time at 7 HST with the formation of bulges (nodules) on the upper surface of the explants.